Environmental Drivers of Seabird At-Sea Distribution in the Eastern South Pacific Ocean: Assemblage Composition Across a Longitudinal Productivity Gradient - Serratosa, Juan; Hyrenbach, K. David; Miranda-Urbina, Diego; Portflitt-Toro, Matías; Luna, Nicolás; Luna-Jorquera, Guillermo (Frontiers in Marine Science, 2020)
Seabird distributions are determined by physical and biological factors operating at variable scales and levels of ecological organization. Accordingly, changes in the composition of the marine avifauna often correspond to large-scale (macro-mega) shifts in water mass properties. Yet, few studies have addressed biogeographical patterns across multiple current systems, spanning from highly-productive to oligotrophic waters. In this study, we characterize the at-sea assemblages of nesting seabirds across the Eastern South Pacific Ocean (ESPO), a vast region spanning from the Humboldt Current to the South Pacific Gyre. Employing multivariate techniques, we first identify four distinct species assemblages and then relate their distributions to the underlying environmental conditions. Our results show that Julian day, depth, sea surface temperature, sea surface salinity, and chlorophyll-α concentration are the most important factors explaining the distribution patterns of these assemblages. Moreover, environmental conditions also explain overall seabird abundance and species richness, two community-level characteristics indicative of ocean productivity. Seabird abundance was best explained by four variables, associated with onshore-offshore gradients (distance to the coast, ocean depth), and the influence of coastal upwelling (mean mixed layer depth, sea surface salinity). Richness was best explained by seasonality (Julian day) and by the presence of water mass boundaries (sea surface temperature coefficient of variation). Our findings underscore the importance of environmental factors structuring the distribution and biogeography of seabirds across gradients of ocean productivity and water mass properties. Understanding the environmental drivers of seabird abundance and richness in the ESPO will inform the prioritization and design of effective marine conservation measures in this poorly studied region.